2005
DOI: 10.1182/blood.v106.11.365.365
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Trial of Lenalidomide (REVLIMID®) with Bortezomib (VELCADE®) in Relapsed and Refractory Multiple Myeloma.

Abstract: Introduction: Bortezomib and lenalidomide are active agents in multiple myeloma (MM), and preclinical data showing additive activity in MM in vitro suggest that enhanced clinical benefit may be derived from combining the two drugs. Bortezomib is approved in MM patients (pts) who have received at least one prior therapy in both the US and EU. Lenalidomide has produced durable responses in the relapsed and refractory MM setting, including in those who received prior bortezomib. Toxicities of bortezomib and lenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…61 The combination of lenalidomide-bortezomib did not increase the risk of VTE in relapsed/refractory patients. 62 The incidence of VTE according to different agents and regimens is summarized in Table 2. Risk factors associated with an increased risk of VTE were the dexamethasone dose and erythropoietin administration.…”
Section: Thrombosis and Lenalidomidementioning
confidence: 99%
“…61 The combination of lenalidomide-bortezomib did not increase the risk of VTE in relapsed/refractory patients. 62 The incidence of VTE according to different agents and regimens is summarized in Table 2. Risk factors associated with an increased risk of VTE were the dexamethasone dose and erythropoietin administration.…”
Section: Thrombosis and Lenalidomidementioning
confidence: 99%
“…24 VATD has been shown to produce a 63% response rate, with 25% complete or near complete responses (M-protein reduction), 22 and recently reported data show that the addition of liposomal doxorubicin to the VTD regimen can increase the response rate to 74%, with 33% complete or near complete responses. 23 Other combinations that have produced high response rates (up to 73%) 25 and complete or near complete response rates (up to 36%) 25 in the relapsed setting include bortezomib plus liposomal doxorubicin alone 37 or with thalidomide, 27 lenalidomide, 26 and melphalan plus thalidomide, with or without steroids. 28,29 The safety profile in these combination studies has been as expected, with no additive toxicities reported, and, in fact, better tolerability described.…”
Section: Bortezomib-based Combinationsmentioning
confidence: 99%
“…A response rate of about 40% has been consistently reported when using thalidomide as a single agent in myeloma patients with refractory or relapsed disease (11)(12)(13)(14)(15)(16)(17). When thalidomide is combined with other anti-myeloma agents the response rate increases to 50-63% (25)(26)(27)(28)(29)(30)(31)(32). However, there is limited information on the duration of such responses.…”
Section: Discussionmentioning
confidence: 99%